Distance Learning and Teacher Education in Botswana: Opportunities and Challenges - Anne L Sikwibele; Judith K Mungoo (International Review of Research in Open and Distributed Learning, 2009)
This paper reports on a study at Molepolole College of Education (MCE) involving teachers and tutors in the Diploma in Primary Education (DPE) program by distance mode, an in-service program aimed at upgrading academic and professional qualifications of primary school teachers in Botswana. The study sought to understand the level of access and the challenges faced by teachers and tutors. Data was collected through in-depth interviews, survey, and document analysis. Findings showed that teachers should be enrolled in the program at a younger age, and issues that lead to delays in completion must be addressed. The paper recommends that the Ministry of Education (MOE) hire full-time tutors to support teachers at their bases, provide resources for practical subjects, organize workshops to familiarize tutors with appropriate strategies for adult learners, increase the duration of residential sessions, explore the use of alternative instructional technologies, and institute regular customer evaluations.